Longitudinal course of hyperintensity on diffusion weighted imaging in adult-onset neuronal intranuclear inclusion disease patients - Liu, Dan; Chen, Kai; Tan, Song; Yin, Long-Lin; Li, Mou; Wang, Yi-Shuang (Frontiers in Neurology, 2023)
Background High signals on diffusion weighted imaging along the corticomedullary junction (CMJ) have demonstrated excellent diagnostic values for adult-onset neuronal intranuclear inclusion disease (NIID). However, the longitudinal course of diffusion weighted imaging high intensities in adult-onset NIID patients has rarely been investigated. Methods We described four NIID cases that had been discovered using skin biopsy and NOTCH2NLC gene testing, after diffusion weighted imaging exhibiting the distinctive corticomedullary junction high signals. Then using complete MRI data from NIID patients, we analyzed the chronological diffusion weighted imaging alterations of those individuals that had been published in Pub Med. Results We discussed 135 NIID cases with comprehensive MRI data, including our four cases, of whom 39 had follow-up outcomes. The following are the four primary diffusion weighted imaging dynamic change patterns: (1) high signal intensities in the corticomedullary junction were negative on diffusion weighted imaging even after an 11-year follow-up (7/39); (2) diffusion weighted imagings were initially negative but subsequently revealed typical findings (9/39); (3) high signal intensities vanished during follow-up (3/39); (4) diffusion weighted imagings were positive at first and developed in a step-by-step manner (20/39). We discovered that NIID lesions eventually damaged the deep white matter, which comprises the cerebral peduncles, brain stem, middle cerebellar peduncles, paravermal regions, and cerebellar white matter. Conclusion The longitudinal dynamic changes in NIID of diffusion weighted imaging are highly complex. We find that there are four main patterns of dynamic changes on diffusion weighted imaging. Furthermore, as the disease progressed, NIID lesions eventually involved the deep white matter.